Coverage and Comprehension: Rabbinical Students and the Study of the Babylonian Talmud. Issue 3 (3rd July 2021) - Kanarek, Jane L.
ABSTRACT: Although Talmud study is central to rabbinical school curriculums, rabbinical students' experiences with Talmud study remain understudied. This article draws on interviews with students from five seminaries to argue that students describe Talmud study as a process of acquiring both knowledge and authenticity. These two goals intersect with a particular tension: a desire to cover large amounts of Talmudic material quickly and a desire to study smaller amounts more slowly. Rather than viewing the latter two as a binary, Talmud teachers should recognize the complex ways in which coverage and comprehension interact with one another, cultivating student and teacher metacognition.